(untitled) (Journal of the College of Basic Education, 2026)
The results of isolation and identification showed the association of the fungal genera Aspergillus, Fusarium, Penicillium, and Rhizopus with stored yellow corn seeds in the districts of Dhi Qar Governorate. The fungus *A. flavus* topped the list of identified fungal species at 37.3%, followed by the remaining fungi at the following percentages: 24.27%, 14.80%, 15.84%, and 7.79%, respectively. Furthermore, the results of the detection of aflatoxin AFB1 using High Performance Liquid Chromatography (HPLC) showed that the most fluorescent isolate had a toxin concentration of 165.8 ppb. Molecular characterization of the most toxin-producing A. flavus isolate showed a match with other A. flavus isolates, and its nucleotide sequence was deposited in GenBank under the code PZ048206. The match with the Indian isolate was 99%. Morphologically, A. flavus was characterized using lactophenol staining, followed by electron microscopy at 40X magnification. The fungal structures (hyphae and spores) appeared dark blue and clearly displayed a spherical head containing numerous spores. Microscopic examination of the lactophenol-stained isolate also revealed several morphological features characteristic of Aspergillus flavus. A long, transparent, smooth-walled conidiophore originating from the hyphae was observed, terminating in a spherical to semi-spherical vesicle. The vesicle is one of the most important diagnostic characteristics of Aspergillus species, as it serves as a base for the formation of conidia, which produce asexual spores.